Entrepreneurial teams and new business creation - Vanaelst, Iris; Wright, Mike , 1952- (Cheltenham, UK ; Northampton, Massachusetts : Edward Elgar, 2009)
Curiosity is focused on how entrepreneurial teams should be formed in order to allow new businesses to be created and to ensure their growth. This title identifies leading contributions to this area and reflects a growing body of research.
1. Team formation and Composition -- 2. Social Interaction and Interpersonal Processes within Teams -- 3. Team Turnover -- 4. Outcome
Includes bibliographical references and index
Keywords: Entrepreneurship; New business enterprises